Advancing circular economy in the pulp and paper sector with novel routes for microbial sulfur recovery - Unay, Elifnaz; Tunay, Dogukan; Ozkaya, Bestami (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
This study presents a novel microbial method for the pulp and paper industry to adopt circular economy practices by converting green liquor, a problematic waste stream, into a valuable energy storage material. Using haloalkaliphilic microorganisms, elemental sulfur is recovered under extreme pH and salinity conditions, achieving concentrations up to 2 g L-1 without chemical pretreatment. The recovered biogenic sulfur was purified and used as a high-value cathode material in lithium-sulfur (Li-S) batteries. Electrochemical tests show an initial specific capacity of approximately 550 mAh g(-1), with redox peaks at similar to 2.3 V, 2.0 V, and 2.5 V, confirming typical Li-S behavior. A multi-criteria decision-making analysis using the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method with AHP-derived weights ranks Li-S batteries highest among other battery chemistries, with a closeness coefficient (Pi) of 0.7352, outperforming alternatives in weight, cost, and energy output. Further research may improve sulfur purity, and electrode performance.
Keywords: Sulfur recovery; Kraft process; Sulfur cathode; Circular economy; MCDM; Li-S; Bio-batteries; CATHODE MATERIALS; Chemistry; Electrochemistry; Energy & Fuels